The synergy between atomically dispersed Pd and cerium oxide for enhanced catalytic properties. Issue 20 (17th May 2017) - Wang, Xue; Chen, Jiayu; Zeng, Jianxin; Wang, Qiuxiang; Li, Zejun; Qin, Ruixuan; Wu, Changzheng; Xie, Zhaoxiong; Zheng, Lansun
Abstract : Atomically dispersed Pd/CeO2 showed excellent activity owing to highly dispersed Pd atoms and the interaction between Pd and CeO2 supports. Abstract : We report a photochemical synthesis of Pd/CeO2 catalysts with atomically dispersed Pd. Compared to atomically dispersed Pd/CeO2 with a cubic CeO2 support (Pd/CeO2 -CP), atomically dispersed Pd/CeO2 with a truncated octahedral CeO2 support (Pd/CeO2 -TOP) exhibited higher activity and selectivity, owing to the synergy between Pd atoms and the (111) surface of CeO2 . When compared to Pd/CeO2 with Pd clusters and nanoparticles via chemical reduction, Pd/CeO2 -TOP showed excellent activity with an enhancement factor of 324 in CO oxidation, as well as an activity enhancement by a factor of 344 in selective oxidation of benzyl alcohol.